Quality of life and symptoms of anxiety and depression in patients affected by ulcerative colitis - Fernandes ACS; Tomazoni EI; Benvegnú DM (Archives of Clinical Gastroenterology - Peertechz Publications, 2020)
Introduction: Ulcerative Colitis (UC) is an Inflammatory Bowel Disease (IBD) that can be divided into two periods: active and remission. Individuals affected by this pathology can manifest symptoms of anxiety and depression, as well as low quality of life, due to the symptomatology of this disease when active. Objective: Demonstrate the relationship between anxiety and depression with UC and its influence on quality of life.  Material and methods: The present study involved 97 individuals affected with UC, who were assessed through the application of the HADS and IBDQ on the social network Facebook, as well as their individual feeds. The survey began after approval by the Research Ethics Committee of the Federal University of Fronteira Sul, upon obtaining informed consent from the patients. Results: The majority of the assisted participants was female, white, married, and residents of southwest Brazil. A prevalence of symptoms of anxiety and depression was observed in individuals with low quality of life and status of disease activity. Discussion: The results show that individuals who exhibited an active disease status presented a lower quality of life, anxiety, and depression.